Flame-made tungsten trioxide loaded zinc oxide nanoparticles in hybrid photovoltaic application - Chawarat Siriwong (2018)
WO3-loaded ZnO nanoparticles containing 0, 0.25, 0.50, 0.75, 1.0 and 3.0 mol% of WO3 were synthesized by Flame Spray Pyrolysis (FSP) from zinc naphthenate and tungsten ethoxide precursors under 5/5 (precursor/oxygen) flame condition. The crystalline phase, morphology and size of pure ZnO and WO3-loaded ZnO prepared by FSP were observed by XRD, BET, TEM and SEM. Moreover, these nanoparticles were successfully applied in hybrid photovoltaic devices as an electron acceptor. Theses devices were fabricated using conjugated polymers Poly(3-hexylthiophene) (P3HT) as an electron donor and poly (3,4-ethylenedioxythiophene): poly (styrenesulfonate) (PEDOT: PSS) as an electrode improver. Exciton dissociation of P3HT/ZnO hybrid photovoltaic that was deposited on an ITO substrate with PEDOT:PSS layer and capped with Al as a metal back electrode, was shown in figure below. The current-voltage characteristic of these devices showed that WO3 could increase the number of photons actually converted to charge carriers that affect the power conversion efficiency. These results concluded that an appropriate amount of WO3 loading could enhance the hybrid photovoltaic efficiency. Especially, the hybrid ZnO/P3HT photovoltaic device with 0.50 mol% WO3-loadeded ZnO as an electron acceptor exhibited maximum power conversion efficiency (η) of 0.411%.